2022
DOI: 10.3390/vaccines10081295
|View full text |Cite
|
Sign up to set email alerts
|

Higher Collective Responsibility, Higher COVID-19 Vaccine Uptake, and Interaction with Vaccine Attitude: Results from Propensity Score Matching

Abstract: Providing both personal and social benefits, vaccination may be motivated by collective responsibility (CR). Some previous studies have indicated the relationship between CR and vaccination but could not exclude confounding bias and had little knowledge about the boundary conditions. This study aimed to examine the association between CR and COVID-19 vaccine uptake and its boundary conditions in an extended version of the theory of planned behavior. A cross-sectional survey with 608 participants from six touri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…These arguments seem to be justified, because, as shown by Johnson et al's research, the risk of illness and severe symptoms is almost four times higher in unvaccinated people [22]. Cosby noticed that being motivated by collective responsibility is more common among medical workers with a rather negative attitude towards vaccinations [23]. A slightly different approach was observed in a hospital in Munich, where surveyed healthcare workers stated that their motivation was mainly to avoid receiving medication in the treatment of infection or that the overall benefits outweighed the risks associated with vaccination [24].…”
Section: Discussionmentioning
confidence: 99%
“…These arguments seem to be justified, because, as shown by Johnson et al's research, the risk of illness and severe symptoms is almost four times higher in unvaccinated people [22]. Cosby noticed that being motivated by collective responsibility is more common among medical workers with a rather negative attitude towards vaccinations [23]. A slightly different approach was observed in a hospital in Munich, where surveyed healthcare workers stated that their motivation was mainly to avoid receiving medication in the treatment of infection or that the overall benefits outweighed the risks associated with vaccination [24].…”
Section: Discussionmentioning
confidence: 99%
“…While there is evidence of success from governments that have stressed the importance of getting vaccinated as a social responsibility and civic duty 40,41 , and several studies have shown the positive association between social responsibility and vaccine intent and uptake [42][43][44] , the 49-fold magnitude of the impact of social responsibility relative to other strategies such as addressing vaccine safety concerns 45 and leveraging descriptive social norms 46,47 is notable. Several factors in turn have significant effects on social responsibility: the expected chance of getting COVID-19 without vaccines, the level of worry about catching COVID-19, and the belief that COVID-19 is dangerous to one's community.…”
Section: Discussionmentioning
confidence: 99%